Genome-Wide Analysis of H3K27me3 in Porcine Embryonic Muscle Development - Tan, Baohua; Wang, Sheng; Wang, Shanshan; Zeng, Jiekang; Hong, Linjun; Li, Zicong; Yang, Jie; Cai, Gengyuan; Zheng, Enqin; Wu, Zhenfang; Gu, Ting (Frontiers in Cell and Developmental Biology, 2021)
The trimethylation of histone H3 lysine 27 (H3K27me3) is one of the most important chromatin modifications, which is generally presented as a repressive mark in various biological processes. However, the dynamic and global-scale distribution of H3K27me3 during porcine embryonic muscle development remains unclear. Here, our study provided a comprehensive genome-wide view of H3K27me3 and analyzed the matching transcriptome in the skeletal muscles on days 33, 65, and 90 post-coitus from Duroc fetuses. Transcriptome analysis identified 4,124 differentially expressed genes (DEGs) and revealed the key transcriptional properties in three stages. We found that the global H3K27me3 levels continually increased during embryonic development, and the H3K27me3 level was negatively correlated with gene expression. The loss of H3K27me3 in the promoter was associated with the transcriptional activation of 856 DEGs in various processes, including skeletal muscle development, calcium signaling, and multiple metabolic pathways. We also identified for the first time that H3K27me3 could enrich in the promoter of genes, such as DES, MYL1, TNNC1, and KLF5, to negatively regulate gene expression in porcine satellite cells (PSCs). The loss of H3K27me3 could promote muscle cell differentiation. Taken together, this study provided the first genome-wide landscape of H3K27me3 in porcine embryonic muscle development. It revealed the complex and broad function of H3K27me3 in the regulation of embryonic muscle development from skeletal muscle morphogenesis to myofiber maturation.